The Effect of Angle of Attack and Flow Conditions on Turbulent Boundary Layer Noise of Small Wind Turbines - AFANASIEVA, Nadiia (Archives of Acoustics, 2017)
The article aims to solve the problem of noise optimization of small wind turbines. The detailed analysis concentrates on accurate specification and prediction of the turbulent boundary layer noise spectrum of the blade airfoil. The angles of attack prediction for a horizontal axis wind turbine (HAWT) and the estimation based on literature data for a vertical axis one (VAWT), were conducted, and the influence on the noise spectrum was considered. The 1/3-octave sound pressure levels are obtained by semi-empirical model BPM. Resulting contour plots show a fundamental difference in the spectrum of HAWT and VAWT reflecting the two aerodynamic modes of flow that predefine the airfoil self-noise. Comparing the blade elements with a local radius of 0.875 m in the HAWT and VAWT conditions the predicted sound pressure levels are the 78.5 dB and 89.8 dB respectively. In case of the HAWT with predicted local angle of attack ranging from 2.98◦ to 4.63◦, the acoustic spectrum will vary primarily within broadband frequency band 1.74–20 kHz. For the VAWT with the local angle of attack ranging from 4◦ to 20◦ the acoustic spectrum varies within low and broadband frequency bands 2 Hz – 20 kHz.